Adolescent Protective Factors for Preventing Electronic Cigarette Use - Ratcliff, Benjamin R. (Journal of drug issues, 2025)
Adolescent electronic cigarette (e-cigarettes) use is a major public health concern. However, there is a relative dearth of literature on factors that prevent the use of e-cigarettes for adolescents. The purpose of the present study was to focus on five protective factors relevant for the prevention of adolescent e-cigarette use. We tested these factors with a large sample of adolescents within a single anlaytic model that allowed for making comparisons among protective factors as well as replicating findings from prior research. Secondary data analysis was conducted on a large sub-sample (n = 33, 193) of data from students who participated in a school survey in the state of Utah. Results from logistic regression indicated that belief in a moral order (OR = 2.30, p < .001), perceived risk of e-cigarette use (OR = 2.22, p < .001), family management (OR = 1.62, p < .001), and commitment to school (OR = 1.43, p < .001) were significantly associated with abstaining from e-cigarette use in the past 30-days. Implications of the findings are discussed in the context of preventing adolescent e-cigarette use.